2020
DOI: 10.17507/jltr.1106.12
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Landscape for Korean Learning: A Survey of Perception, Attitude, and Practice of Korean Beginners at a Korean University

Abstract: This study aimed to investigate the perception of, attitude to and practice of linguistic landscape for Korean learning among the international Korean beginners. A questionnaire as a self-assessment instrument was given to a group of 41 international university students with lower Korean language proficiency studying in a Korean university. The descriptive statistics indicated that for perception, although they pay attention to English the most, they could also notice Korean and Romanized Korean on the linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…We believe that it is likely that a number of our participants belong to the GLL category as students of applied linguistics simultaneously learning multiple languages. In particular, our results correspond to the outcomes reported in a study of perceptions of Korean LL by 41 international beginner Korean students (Qi, Zhang, Sorokina, 2020) who showed a preference for English LL over Korean and Romanised Korean LL. At the same time, a qualitative study of three Korean students (Chestnut, Lee, Schulte, 2013) revealed that even though the investigated learners majored in English, they did not pay attention to English.…”
Section: Discussionsupporting
confidence: 89%
“…We believe that it is likely that a number of our participants belong to the GLL category as students of applied linguistics simultaneously learning multiple languages. In particular, our results correspond to the outcomes reported in a study of perceptions of Korean LL by 41 international beginner Korean students (Qi, Zhang, Sorokina, 2020) who showed a preference for English LL over Korean and Romanised Korean LL. At the same time, a qualitative study of three Korean students (Chestnut, Lee, Schulte, 2013) revealed that even though the investigated learners majored in English, they did not pay attention to English.…”
Section: Discussionsupporting
confidence: 89%
“…Students' active involvement, as well as that of teachers, sometimes adds layers to the landscape inside schools where professionalism such as accuracy of language usage is not required, unlike official signs displayed in public spaces that have to be written in an appropriate way (Gorter and Cenoz 2015b;Im 2020). The schoolscape is also a place for language learning (Sayer 2010;Qi, Zhang, and Sorokina 2020). For example, language learners can develop criticality in response to the presence of languages in terms of dominance and marginalisation (Barrs 2015;Sayer 2010) and are immersed in authentic language to develop their proficiency (Malinowski 2010).…”
Section: Linguistic Landscape As a Site Of Identity Expressionmentioning
confidence: 99%
“…LL was introduced by Landry & Bourhis in 1997 which pays special attention to the various written languages that appear on public road signs, billboards, street names, place names, commercial shop signs, and general signs on buildings. Government in a region, region, or urban agglomeration [4]. According to Groter (2006), it is explained in more detail that the linguistic landscape analyzes the use of textual formatted language that is displayed and presented outside the public sphere, including the use of various signs that are displayed along with the language [5,6].…”
Section: Introductionmentioning
confidence: 99%